2020
DOI: 10.1016/j.tafmec.2020.102736
|View full text |Cite
|
Sign up to set email alerts
|

Toughness or strength? Regularization in phase-field fracture explained by the coupled criterion

Abstract: In recent years the phase-field method and the coupled energy and stress-based criterion have attracted much attention due to their adaptability in modeling fractures. Both approaches have been successfully used to determine crack initiation and have compared well with real-life experiments. The phase-field method diffuses the crack surface into the volume of the solid, thus making the solution viable through variational techniques. The diffusion is controlled by an internal length scale, which is primarily co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 99 publications
4
40
0
Order By: Relevance
“…where K Ic is the material fracture toughness. It has been shown that the consideration of a finite > 0 + enables to accurately predict crack nucleation, capturing its transition from strength-driven to fracture-driven (Tanné et al, 2018), and in agreement with the predictions from the coupled criterion in finite fracture mechanics (Molnár et al, 2020a).…”
Section: Phase Field Fracture Modelsupporting
confidence: 54%
“…where K Ic is the material fracture toughness. It has been shown that the consideration of a finite > 0 + enables to accurately predict crack nucleation, capturing its transition from strength-driven to fracture-driven (Tanné et al, 2018), and in agreement with the predictions from the coupled criterion in finite fracture mechanics (Molnár et al, 2020a).…”
Section: Phase Field Fracture Modelsupporting
confidence: 54%
“…Thus, our findings demonstrate that phase field models without an elastic phase can also reconcile toughness and strength. The capabilities of variational phase field models in incorporating the concepts of material strength and toughness bring them in agreement with the coupled criterion of finite fracture mechanics [64,65], but with the additional modelling capabilities intrinsic to phase field models. Along these lines, several modelling strategies and constitutive prescriptions have been presented to enhance the crack nucleation capabilities of phase field models and decouple the strength and the phase field length scale [43,66,67].…”
Section: Discussionmentioning
confidence: 99%
“…(21). Note that similar arguments hold also for the length scale parameter related to the Phase Field approach, whose connection with l c was investigated in [37].…”
Section: Discussion Of Resultsmentioning
confidence: 60%